2017
DOI: 10.1097/rlu.0000000000001718
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Comparison of Contrast-Enhanced FDG PET/CT and 64-Slice Multi–Detector-Row CT for Initial Staging and Response Evaluation at the End of Treatment in Patients With Lymphoma

Abstract: ObjectivesTo compare staging correctness between contrast-enhanced FDG PET/ceCT and 64-slice multi–detector-row CT (ceCT64) for initial staging and response evaluation at the end of treatment (EOT) in patients with Hodgkin lymphoma, diffuse large B cell lymphoma (DLBCL), and follicular lymphoma.MethodsThis prospective study compared initial staging and response evaluation at EOT. One hundred eighty-one patients were randomly assigned to either ceCT64 or FDG PET/ceCT. A nuclear medicine physician and a radiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 29 publications
(32 reference statements)
1
14
0
1
Order By: Relevance
“…Thus, PET/CT and contrast-enhanced computed tomography were concurrent in results in 55% of cases during treatment and 75% at the end of treatment with CT sensitivity of 61.1%, specificity of 92.2%, and accuracy of 76.2% during treatment in comparison to 100% sensitivity and specificity of PET/CT, while sensitivity of CT at end of treatment is 57.5% with specificity of 86.7% and accuracy of 71.6%. This is in keeping with the multicenter study; comparison of FDG PET/CT and 64-slice multidetector-row CT was done in initial staging and response evaluation at the end of treatment in patients with lymphoma by Gómez León et al [13]; 181 patients were enrolled; their results confirmed that FDG PET/ CECT was clearly superior to ceCT64 for EOT evaluation (P < 0.05). Using FDG PET/CT, there was concordance with the reference standard in 97.8% of the cases (88/90) with κ = 0.91 (P < 0.001), corresponding with a CR in 83.3% (n = 75), a PR in 4.4% (n = 4), and a PD in 10% (n = 9), with good sensitivity and specificity for response assessment.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, PET/CT and contrast-enhanced computed tomography were concurrent in results in 55% of cases during treatment and 75% at the end of treatment with CT sensitivity of 61.1%, specificity of 92.2%, and accuracy of 76.2% during treatment in comparison to 100% sensitivity and specificity of PET/CT, while sensitivity of CT at end of treatment is 57.5% with specificity of 86.7% and accuracy of 71.6%. This is in keeping with the multicenter study; comparison of FDG PET/CT and 64-slice multidetector-row CT was done in initial staging and response evaluation at the end of treatment in patients with lymphoma by Gómez León et al [13]; 181 patients were enrolled; their results confirmed that FDG PET/ CECT was clearly superior to ceCT64 for EOT evaluation (P < 0.05). Using FDG PET/CT, there was concordance with the reference standard in 97.8% of the cases (88/90) with κ = 0.91 (P < 0.001), corresponding with a CR in 83.3% (n = 75), a PR in 4.4% (n = 4), and a PD in 10% (n = 9), with good sensitivity and specificity for response assessment.…”
Section: Discussionsupporting
confidence: 71%
“…While our study is limited by its modest cohort size, this was a hypothesis-generating study, as [ 18 F]FDG/PET is not considered a routine procedure for MALT lymphoma according to the ICML guidelines [9]. The fact that-contrary to our own institutional standard of care-CT is still the standard test for MALT lymphomas in the vast majority of institutions, despite its known limitations for treatment response assessment in lymphomas [21], prevented us from using a multi-centric approach that would have increased the number of study participants. For the survival analysis, we did not further subdivide our patient population (e.g., into gastric and non-gastric lymphomas), because only 12/61 patients overall, and 6/35 patients in the CD20-antibody group, showed progression.…”
Section: Discussionmentioning
confidence: 99%
“…Since the late 1990s, a number of studies have consistently demonstrated the high NPV of end-of-treatment PET and underlined its value for this application, particularly in Hodgkin lymphoma [54][55][56][57][58][59][60]. Spanish researchers examined 37 subjects with follicular lymphoma, as well as 72 Hodgkin lymphoma and 72 DLBCL patients, in order to compare the diagnostic performance of CT and FDG-PET/CT [13]. While CT was concordant with the defined reference methods in only 78% of cases, FDG-PET/CT showed an excellent agreement rate of 97.8%.…”
Section: Late Response Evaluationmentioning
confidence: 99%
“…Despite significant advances in the management of this malignancy, cure rates are still generally lower than for Hodgkin lymphoma, with approximately one-third of all individuals failing front-line therapy. Due to its superior sensitivity in the detection of nodal and extra-nodal lymphoma manifestations, FDG-PET is strongly recommended for staging patients with DLBCL [13]. Moreover, several international trials have examined whether PET imaging may be used early during treatment to separate individuals needing therapy intensification from good responders, that is, candidates for de-escalation [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%